2011
DOI: 10.1007/s10409-011-0400-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of an offshore pipe laying operation using the reel method

Abstract: A system designed for a rigid and flexible pipe laying purposes is presented in the paper. Mathematical and numerical models are developed by using the rigid finite element method (RFEM). The RFEM is an efficient solution in the time domain. Static and dynamic problems related to pipe installation are solved by taking the advantage of simple interpretation and implementation of the method. Large deformations of the pipe during spooling and when it is reeled out at sea are considered. A material model implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The procedure for calculation of moments (vectors M i ) acting on segments i − 1 and i is different from the approaches used in previous papers [52][53][54] and [58][59][60].…”
Section: Energy Of Spring Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for calculation of moments (vectors M i ) acting on segments i − 1 and i is different from the approaches used in previous papers [52][53][54] and [58][59][60].…”
Section: Energy Of Spring Deformationmentioning
confidence: 99%
“…RFEM formulated in joint coordinates is also applied by Szczotka [52][53][54][55] for dynamic analysis of offshore pipeline installations with special emphasis on the following installation techniques: S-lay, J-lay and reel lay.…”
Section: Introductionmentioning
confidence: 99%
“…Notable HMs have been considered in recent studies as reported in Amaechi [110][111][112][113][114], and Tonatto [115][116][117][118][119] which considered the statics and dynamics of hoses in separate presentations. In the study by Szczotka [120], an HM was presented with a numerical model developed using a rigid finite element model (RFEM) for the static and dynamic reeling operation in pipe-laying. The study showed that by using this model, active and passive tensioner reels could be studied and the reeling installation of pipelines in sea conditions could be simulated well, as validated via a pipe laying simulation with an active reel drive.…”
Section: Introductionmentioning
confidence: 99%
“…With considerable attention has been paid to the security and reliability of flexible structures in the installation and operation phases [15][16][17][18][19], research on their mechanical behavior during early reeling operation rarely shows in the open literature according to our review, although some similar study regarding reel-laying manipulation might provide some references. Szczotka [20] adopted the rigid finite element method to present the static and dynamic response of an offshore pipe reel-laying process. The failure phenomenon has also been observed in reel-laying manipulation.…”
Section: Introductionmentioning
confidence: 99%